Pemanfaatan Sampah sebagai Alat Peraga Edukatif bagi Siswa PAUD - Siti Aliyah; Mufid Mufid; Purwo Adi Wibowo (Universitas Islam Nahdlatul Ulama Jepara, 2017)
AbstractThe development of quality early childhood is a major investment that are important in human development in Indonesia. To support the creativity of learners is needed media as a supporter, which in this case former students trash useless can be used as an educational tool at the same props for students learning about environmental awareness. Partners service is namely PAUD PERMATA Darul Hikmah and PAUD Roudlotul Faizin both of which are located in the district of Jepara. The purpose of this service program is improving the quality of learning with the use of waste as educational props to stimulate the creativity of students. The activities have been carried out through training to teachers and early childhood learning groups or managers in both partners. Outcomes of these activities in the form of products props educative (APE) in the form of sheep originating from waste bottles of milk drinks, bottled soft drinks, which transformed into turtles, fish , owl, and piggy bank